An infected late miscarriage associated with a genetically determined enhanced immune response in patients with recurrent viral and bacterial infections - L Sh Tsechoeva; R I Glushakov; N I Tapilskaya (IP Berlin A.V., 2018)
Microbiological and genetic examinations of patients previously treated for an infected late miscarriage were performed. Materials and methods. Women (n=36) with viral excretion of cytomegalovirus, bacterial vaginosis, two or more relapses of herpes virus infection localized in the genital area within 6 months, and absence of any other reproductively significant infections were selected. All patients underwent vaginal microbiocenosis studies in dynamics, as well as polymorphisms associated with the enhanced immune response, NOS3 (4a/4b), PAI-1 (4G/5G), IL1B (C3954T, C511T), TNFA (G238A, G308A), PPARG (Pro12Ala), PGC1A (Gly482Ser), GSTM1 (del), GSTT1 (del), MMP1 (1G/2G). Results. In the course of the correlation analysis within the group between qualitative signs (recurrent bacterial vaginosis) and the presence of genetic polymorphisms, it was established that the presence of polymorphisms in matrix metalloproteinase - collagenase-1 (r=0.59) and tumor necrosis factor a (r=0.51) genes is associated with a recurrent course bacterial vaginosis. There is no reliable correlation between the polymorphism of the studied genes and the virus release of the cytomegalovirus. The conclusion. As a preparation for pregnancy, patients with an infected miscarriage in anamnesis or with recurrent viral and bacterial infections require the appointment of therapy aimed at regulating the immune response. One of the drugs of choice is inosine pranobex (Isoprinosine®), which stimulates cellular immune response that contributes to a change in the cytokine profile and increases the functional activity of the effector cells.